Perception, Attitude, and Learning Preferences Regarding Shloka Pathan among BAMS Students: A Cross-Sectional Study - Dr. Vidyavati Hiremath; Dr. Jayvant Vasant Kharat (The Bioscan, 2026)
Shloka Pathan forms the foundation of Ayurvedic education and plays an important role in developing memory, pronunciation, and discipline among students. However, variations in learning experiences, perceived difficulty, and anxiety during recitation are commonly observed.